Experimentation in the work of director Sami Abdel Hamid The play "Beit Barna Rada Alba" as a model (Journal of the College of Basic Education, 2022)
The research deals with the subject of experimentation in the work of theater director Sami Abdel Hamid, because it occupies an important position in his directorial experience, as it divides the totality of his work into two types, the gap between which has diverged, namely:Theatrical performances directed according to the traditional methods of theatrical directingTheatrical works that he directed experimentally.The researcher will try to confine himself to studying the work of the "experimental" director, defining his motives and the reasons for his orientation and the extent of their impact on the work of the theatrical director in terms of their contribution to the establishment of the Iraqi theatrical artistic taste.In this research, the researcher will try to address a problem that has long plagued theatrical activity in Iraq. The problem of sharp contrast in the levels of the creative process,